2009
DOI: 10.1002/art.24305
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of interleukin‐33 signaling attenuates the severity of experimental arthritis

Abstract: Objective. Interleukin-33 (IL-33; or, IL-1F11) was recently identified as the ligand of the IL-1 family receptor T1/ST2. The aim of this study was to examine IL-33 production in human and mouse joints and to investigate the role of IL-33 and T1/ST2 in experimental arthritis.Methods. IL-33 expression was examined in human synovial tissue, rheumatoid arthritis (RA) synovial fibroblasts, and arthritic mouse joints. Mice with collagen-induced arthritis (CIA) were treated with blocking anti-ST2 antibody or control … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

17
267
2
3

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 287 publications
(289 citation statements)
references
References 44 publications
(32 reference statements)
17
267
2
3
Order By: Relevance
“…Several immunohistochemical experiments showed that IL-33 is located in the nucleus of endothelial, epithelial and fibroblast cells [21,22,29], where, like IL-1α, it may exert a transcriptional activity [29].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Several immunohistochemical experiments showed that IL-33 is located in the nucleus of endothelial, epithelial and fibroblast cells [21,22,29], where, like IL-1α, it may exert a transcriptional activity [29].…”
Section: Discussionmentioning
confidence: 99%
“…Mice administered intra-articularly with bovine serum albumin exhibited hypernociception which was blocked by sST2 [33]. In addition, IL-33 was recently shown to exacerbate antigen-induced arthritis by activating bone marrow-derived mast cells [34], and administration of a blocking anti-ST2 antibody attenuated the severity of collagen-induced arthritis [22,35].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…IL-33 [previously known as nuclear factor from high endothelial venule or NF-HEV (4,5)], is a chromatin-associated nuclear cytokine from the IL-1 family (6, 7), which has been linked to important diseases (8)(9)(10), including asthma (11), rheumatoid arthritis (12,13), ulcerative colitis (14), and cardiovascular diseases (15).…”
mentioning
confidence: 99%